2010
DOI: 10.1021/ie101192a
|View full text |Cite
|
Sign up to set email alerts
|

Reburning in Oxy-Fuel Combustion: A Parametric Study of the Combustion Chemistry

Abstract: The present work investigates reburning reduction of nitrogen oxides in oxy-fuel combustion by means of a detailed reaction mechanism applied to a plug-flow reactor. Reburning reactions, which are known to convert NO x into N 2 , are of special interest in oxy-fuel combustion due to extensive recirculation of flue gases, including NO x , to the flame. Furthermore, the high concentration of carbon dioxide in oxy-fuel combustion is known to influence the radical pool (H/O/OH), which is critical to the combustion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 17 publications
1
45
0
Order By: Relevance
“…3a) and the major nitrogen species (NO and HCN; Fig. 3b) calculated with N 2 and CO 2 as bulk gas (Normann et al, 2010). The oxidation rate of the fuel is lowered by CO 2 ; the peak concentration of hydrocarbon radicals (CH 1-3 ) is lower and the residence time in the reducing zone (Stage I) is longer.…”
Section: Chemical Effects On Reburning In Oxy-fuel Combustionmentioning
confidence: 98%
See 2 more Smart Citations
“…3a) and the major nitrogen species (NO and HCN; Fig. 3b) calculated with N 2 and CO 2 as bulk gas (Normann et al, 2010). The oxidation rate of the fuel is lowered by CO 2 ; the peak concentration of hydrocarbon radicals (CH 1-3 ) is lower and the residence time in the reducing zone (Stage I) is longer.…”
Section: Chemical Effects On Reburning In Oxy-fuel Combustionmentioning
confidence: 98%
“…Furthermore, the reduction of NO by char is enhanced by the presence of CO, and the reduction could, thus, be of special interest in oxy-fuel combustion where the CO concentration is locally increased. The authors of this work have previously performed a series of investigations on the emission of nitrogen oxides from oxy-fuel combustion Kühnemuth et al, 2011;Normann et al, 2008Normann et al, , 2009Normann et al, , 2010. From the results it was concluded that the emission of nitrogen oxides, related to the amount of fuel supplied, is significantly reduced in oxy-fuel combustion compared to air-firing, because of increased reduction of formed and recycled NO x .…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Alongside the sulfur chemistry, nitrogen chemistry in oxy-combustion has also been a focus of several studies (Croiset and Thambimuthu, 2001;Gimenez-Lopez et al, 2010;Glarborg et al, 2003;Kimura et al, 1995;Kuhnemuth et al, 2010;Liu et al, 2005;Tree, 2009, 2012;Mendiara and Glarborg, 2009;Normann et al, 2009Normann et al, , 2010Normann et al, , 2011Obras-Loscertales et al, 2015;Okazaki and Ando, 1997;Watanabe and Okazaki, 2011). Experiments revealed the emission of nitrogen oxides (NO x ) to be significantly lowered in oxy-combustion comparing to that of air-combustion (Croiset and Thambimuthu, 2001;Kimura et al, 1995;Liu et al, 2005).…”
Section: So 3 + H 2 O → H 2 So 4 R(4)mentioning
confidence: 99%
“…7. However, the methane oxidation follows the three major routes through CH 2 O or CH 2 and the recombination of CH 3 [28]. CH 3 may be consumed through R10 (O þ CH 3 ]H þ CH 2 O) with production of CH 2 O or through R97 (OH þ CH 3 ] CH 2 (s) þ H 2 O) with production of CH 2 , and recombined to CH 4 via R52 (H þ CH 3 þ M]CH 4 þ M, M: third body).…”
Section: N 2 -Dilution Air-methane Flamementioning
confidence: 99%